2019
DOI: 10.1177/0266242618811893
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and family business performance: The joint effect of environmental dynamism and national culture

Abstract: Building on the entrepreneurial orientation (EO) literature, we investigate the relationship between family firm performance and autonomy, a key EO dimension. To enhance the understanding of the role of autonomy, we compare the joint impact of environmental dynamism and national cultural context (performance-based vs socially supportive cultures) on the autonomy–performance relationship of family firms in the United States and Taiwan. Using a configurational approach and data from 130 family firms (53 in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 142 publications
(192 reference statements)
4
37
0
Order By: Relevance
“…In other words, MSMEs are unable to cope with product change requested by dynamic market. This confirms the finding that the bigger the company is, the more adaptive it is to cope with dynamic environment (Yu, Lumpkin, Parboteeah, and Stambaugh, 2019). The research shows that highly dynamic environment may negatively influence company"s performance (Davis, Eisenhardt, and Bingham, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…In other words, MSMEs are unable to cope with product change requested by dynamic market. This confirms the finding that the bigger the company is, the more adaptive it is to cope with dynamic environment (Yu, Lumpkin, Parboteeah, and Stambaugh, 2019). The research shows that highly dynamic environment may negatively influence company"s performance (Davis, Eisenhardt, and Bingham, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…The empirical discoveries associated with autonomy, namely entrepreneurial orientation dimension, result, and conclusion appear to be inconsistent in the study by Yu, Lumpkin, Praveen Parboteeah, and Stambaugh (2019). Chen, Neubaum, Reilly, and Lynn (2014) and Jancenelle, Storrud-Barnes, and Javalgi (2017) show a positive correlation among autonomy and firm performance.…”
Section: Autonomy and Firm Performancementioning
confidence: 90%
“…Competitive aggressiveness is considered to be an establishment's ability to execute superior strength than opponents (Yu et al, 2019;Kuivalainen, Sundqvist, & Cadogan, 2010). It is categorised as a positive response to modest threats (Rauch et al, 2009) and competitive behaviour (Lyon et al, 2000).…”
Section: Competitive Aggressiveness and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding the dynamics of the business environment has revealed the sporadic factors that are involved in the business environment dynamism. Miller and Friesen developed a five-item scale for environmental dynamism (9), which has been adopted by several authors (10,11). Furthermore, Achrol and Stern have developed a questionnaire with four items to describe the extent of changes/variability in the membership in electronic mar-ketplaces, competitive behavior, customer behavior, and technical knowledge base (12).…”
Section: Introductionmentioning
confidence: 99%